Edukasi Pentingnya Visi dan Misi Pelayanan dalam Merancangkan Program Pelayanan Rohani Kristen (RohKris) di Sekolah Negeri Mitra Perkantas Lampung - Esteria FA Situmorang (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
Student life at school is a colorful life. At school students are filled with knowledge in order to think critically and have soft skills in organizations including religious organizations. Students' disinterest in religious activities can be caused by their lack of understanding of the importance of vision - mission and SWOT analysis in service which will have an impact on the difficulty in designing service programs. Vision and mission are fundamental things needed to be able to determine goals, objectives and make service programs. Therefore, Perkantas Lampung as a school partner conducts coaching in the form of counseling and workshops to help school fellowship administrators in formulating a vision - mission and also planning a service program for the school fellowship. Based on the worksheets provided, the student leaders were finally able to start thinking about the simple things needed in building a Christian student fellowship in their school.